Functional morphology of the horseshoe spot in the frustule of Planothidium species (Bacillariophyta) - Bukhtiyarova, L.M.; Lyakh, A.M. (Український ботанічний журнал, 2014)
Morphology of the horseshoe spot (HHS) with the cavity has been investigated in details in several species of Planothidium Round et Bukht. that carry out an attached mode of life. On the base of photomicrographs obtained with light and scanning electron microscopy, the model of the HSS longitudinal section was designed and light rays tracing through it has been implemented. It has been shown that HHS is an optical system that may diffuse or focus light, depending on the refractive index of the matter inside the cavity. For the first time HHS functions are revealed in a living diatom organism: diffusion of light over the chloroplast side turned to the substrate. The vertical part of inner convexity generates on the attached valve the heating arc that provides a diatom cell with additional heating energy. Thus, a new mechanism of light utilization was detected in the diatom species widely distributed in benthic ecosystems. A new term, lensoid, and terminology for its morphological description are proposed.